Advances in the Regulation of Mammalian Follicle-Stimulating Hormone Secretion - Hao-Qi Wang; Wei-Di Zhang; Bao Yuan; Jia-Bao Zhang (Animals, 2021)
Mammalian reproduction is mainly driven and regulated by the hypothalamic-pituitary-gonadal (HPG) axis. Follicle-stimulating hormone (FSH), which is synthesized and secreted by the anterior pituitary gland, is a key regulator that ultimately affects animal fertility. As a dimeric glycoprotein hormone, the biological specificity of FSH is mainly determined by the β subunit. As research techniques are being continuously innovated, studies are exploring the underlying molecular mechanism regulating the secretion of mammalian FSH. This article will review the current knowledge on the molecular mechanisms and signaling pathways systematically regulating FSH synthesis and will present the latest hypothesis about the nuclear cross-talk among the various endocrine-induced pathways for transcriptional regulation of the FSH β subunit. This article will provide novel ideas and potential targets for the improved use of FSH in livestock breeding and therapeutic development.